2016
DOI: 10.1007/s00415-016-8136-x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin treatment failures in cervical dystonia: causes, management, and outcomes

Abstract: Botulinum toxin (BoNT) is highly effective in the treatment of cervical dystonia (CD), yet a significant proportion of patients report low levels of satisfaction following treatment and fail to follow-up for repeated treatments. The goal of this study was to determine the reasons some patients have unsatisfactory responses. A total of 35 subjects who came to our center requesting alternative treatments due to unsatisfactory responses following BoNT treatment for CD were evaluated. Included were 26 women and 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 37 publications
(43 reference statements)
2
84
0
2
Order By: Relevance
“…As mentioned above, up to 78 % of patients receiving repeated injections had satisfactory responses following a mean number of 2 trials [1]. However, this could range from 1 to 8 trials [1].…”
Section: Dear Sirsmentioning
confidence: 92%
See 3 more Smart Citations
“…As mentioned above, up to 78 % of patients receiving repeated injections had satisfactory responses following a mean number of 2 trials [1]. However, this could range from 1 to 8 trials [1].…”
Section: Dear Sirsmentioning
confidence: 92%
“…They found that unsatisfactory outcomes were largely driven by suboptimal BoNT doses, wrong muscle targeting, and/or complex movement patterns [1]. Only one patient was functionally resistant to BoNT [1]. Notably, the majority of patients (about 78 %) receiving repeated injections reached a satisfactory response after adjusting BoNT dosing and/or muscle targets, indicating the final outcomes crucially relied on the involved physicians' expertise [2].…”
Section: Dear Sirsmentioning
confidence: 96%
See 2 more Smart Citations
“…Common determinants for an unsuccessful chemodenervation session/poor responder include suboptimal doses, suboptimal muscle targeting, intolerable side efects, and complex movement paterns, discordant expectations, and an incorrect diagnosis [46].…”
Section: Challenges With Bont Therapymentioning
confidence: 99%